P078 A genetic variant of IL-32 is associated with the ex vivo cytokine production of ANTI-TNF treated pbmcs isolated from rheumatoid arthritis patients. (21st February 2018) - Popa, C; Damen, M; Schraa, K; Tweehuysen, L; den Broeder, A; Netea, M; Joosten, L
Abstract : Introduction: Since the introduction of biologics in the treatment of rheumatoid arthritis (RA) disease outcome improved. Still, about 40% of RA patients do not respond to therapy with TNFα blockers. Previously, a strong link between TNFα and interleukin (IL)−32 has been reported in RA. 1 Objectives: We hypothesise that a promoter single nucleotide polymorphism (SNP) in IL-32 can affect clinical responsiveness to anti-TNFα treatment in RA patients, functioning as a new biomarker in treatment of RA. 2 Methods: Peripheral mononuclear cells (PBMCs) from RA patients and healthy individuals were stimulated with RPMI or recombinant human (rh)TNFα to study the mRNA and protein expression of IL-32 and other pro-inflammatory cytokines. Moreover, disease activity scores (DAS28), ' in vitro response ' and clinical response to anti-TNFα therapy (etanercept, adalimumab), of RA patients were measured and all were stratified for the IL-32 SNP (C/T). Results: Stimulation of PBMCs from RA patients was followed by higher IL-32 protein production and a tendency towards higher IL-32β and IL-32γ mRNA expression compared to healthy individuals. When data was stratified for the IL-32 promoter SNP, patients bearing the CC genotype showed higher IL-32 protein expression. Of interest, these patients also produced more cytokines. Even though the DAS28 did not depend on the presence of the promoter SNP, the ' ex vivo' cytokine response did have a different pattern in clinical responders depending on the genotype. Conclusions: IL-32 mRNA and protein production was higher in RA patients compared to healthy individuals, with a trend towards higher concentrations in patients bearing the CC genotype. Regardless of the fact that the promoter SNP was not associated with disease activity, IL-1 beta production in the CC-genotype might predict clinical response to either etanercept or adalimumab. References: . Heinhuis B, et al. Ann Rheum Dis2011;70:660–7. . Damen MS, et al. Sci Rep2017;7:41629. Disclosure of interest: None declared